(untitled) (Comparative & International Education Series, 2021)
As Historically Black Colleges and Universities (HBCUs) rethink their internationalization plans and re-evaluate institutional readiness, faculty readiness needs to be at the top of the discussion. In the past, little attention has been given to faculty readiness as institutions considered their internationalization plans. This chapter provides questions for institutions to consider around faculty readiness and provides a faculty readiness model to guide universities in their internationalization efforts.